Pandemi dan Krisis Multidimensi: Studi Kasus Permasalahan Gender di Tengah Pandemi COVID-19 - Supartinah, Supartinah; Anwar, Ahmad (Department of International Relations, Brawijaya University, 2021)
This paper emphasizes that the Covid-19 pandemic is not just a health issue. It has caused a global economic crisis and most importantly a negative impact on gender inequality. The data was collected mainly from the UN Women and projected using content-analysis methods. Using a gender perspective, this study explains that the gender issues as a result of this crisis arise from economic activities that are not distributed fairly. In turn, this has spread to social lives of men and women with significantly more exposed women which are enforced in almost all countries. Job losses and the quality of life for both men and women have decreased. They are forced to make ends meet with increasingly limited resources. This can hamper the ongoing efforts on women's rights fulfilment and gender equality. Keywords: Covid – 19, Economic Crisis, Gender Issue